Numerical study of the effects of hydrodynamic interactions among cells for microfluidic holographic cyto-tomography - Vitolo, Angela; Villone, Massimiliano M.; Maffettone, Pier Luca (Frontiers in Physics, 2024)
When cells in a suspension flow through a microfluidic channel and rotate within the field of view (FOV) of a holographic microscope, they become accessible to a light beam from various angles. This allows the retrieval of a three-dimensional refractive index map for each flowing cell, essentially a 3D phase-contrast tomogram. Understanding the effects of hydrodynamic interactions among cells on their rotational behaviour during flow is crucial for designing microfluidic devices for holographic imaging. In this study, we employ direct numerical simulations to investigate the dynamics of cell clusters suspended in a Newtonian liquid under pressure-driven flow within a microfluidic channel, with the aim of clarifying the influence of hydrodynamic interactions on cell rotation.